Signage and wayfinding design a complete guide to creating environmental graphic design systems - Calori, Chris; Vanden-Eynden, David 1951-. (Hoboken, NJ John Wiley & Sons, Inc., 2015)
"Covers development of room/space numbering systems, approaches to sign typing and numbering, and message schedule management"-- Provided by publisher.
What Is Environmental Graphic Design? -- The Spectrum of EGD Activity -- The Importance of EGD Today -- Digital Information Systems and EGD -- You Can't Learn This in College -- What's Ahead in This Book -- The Design Process -- The Client Is Part of the Process -- The Design Process Applied to EGD -- Phase 1: Data Collection and Analysis (Predesign) -- Phase 2: Schematic Design -- Phase 3: Design Development -- Phase 4: Documentation -- Phase 5: Bidding (Postdesign) -- Phase 6: Fabrication/ Installation Observation -- Phase 7: Postinstallation Evaluation -- Chapter Wrap-Up -- Overview of the Signage Pyramid Method -- Genesis of a Design Approach -- The Signage Pyramid's Component Systems -- The Signage Pyramid and Resource Allocation -- Chapter Wrap-Up -- The Information Content System -- Kinds of Sign Information Content -- Hierarchy of Content -- Developing the Sign Information Content System -- Navigation: Message Hierarchy and Proximity -- Other Factors Affecting the Sign Information Content System -- Pictorial information Content -- Signage Master Plans -- Chapter Wrap-Up -- The Graphic System -- Typography Overview -- Choosing a Typeface -- Typographic Treatment -- Typographic Considerations in Signage for People Who Read by Touch -- Symbols and Arrows -- Diagrams -- Other Graphic Elements -- Color -- Layout -- Overview of Sign Graphic Application Processes -- Chapter Wrap-Up -- The Hardware System -- Shape -- Connotations of Form -- Sign Mounting Considerations -- Sign Size Considerations -- Sign Lighting Overview -- Sign Materials Overview -- Basic Sign Materials -- Electronic Digital Display Units -- Stock Sign Hardware Systems -- Sign Materials and Codes -- Overview of Sign Coatings and Finishes -- Chapter Wrap-Up.
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Computer graphics; Communication in architectural design; Graphic arts